Restorying "Caring" in Education:: Students’ Narratives of Caring for and about - McKamey, Corinne (Narrative Matters, 2011)
In this paper, I use two exemplary narrative case studies to illustrate the multiple ways caring functioned for students in their urban high school context. One case study illustrates how different frames of caring can provide different interpretations of a situation. Another case study shows how caring processes can act in synergistic ways. I conclude by arguing that we should widen our conception of educational care to be inclusive of the complex and overlapping ways that students engage in processes of caring for and caring about.